Drivers for improving supply chain performance: an empirical study. (9th January 2006) - Hofmann, Paul; Reiner, Gerald
A lot of innovation happening nowadays is not so much in the products as in the processes. The importance of integrated, globally optimised supply chains is well understood. Executives have discovered the impact on business performance that can be achieved by effectively managing their supply chains. Nevertheless, a recent study shows that only a fraction of today's supply chains are managed efficiently. One important reason is the mounting challenges faced by executives. These include globalisation and outsourcing, a significant increase in supply and demand uncertainties, more products with short life cycles and the proliferation of products in today's markets. We will identify measures to characterise the business performance as well as supply chain effectiveness and develop measures to characterise the level of maturity of the business process and the information technology employed by a company. Our objective in this research is to identify enablers that allow companies to manage their supply chains so as to maximise business performance. We focus on two classes of enablers: business processes and information technology.